A new species of seed-harvester ant in the genus Pogonomyrmex (P. brevibarbis group) with ergatoid queens and intercastes from the Andes of Argentina (Hymenoptera: Formicidae: Myrmicinae) - Johnson, Robert A. (Zootaxa, 2025)
South American species of seed-harvester ants in the genus Pogonomyrmex are interesting biologically because of their numerous queen phenotypes and life histories. This paper describes Pogonomyrmex eremicus n. sp., which belongs to the P. brevibarbis group. Pogonomyrmex eremicus is the first described species in the P. brevibarbis group to have ergatoid queens, and it also has intercastes with ergatoid queens, as opposed to alate queens. These intercastes all have similar morphology and none are intermediate to workers and ergatoid queens in size—rather they completely overlap with workers for four morphological measures (head width, head length, mesosoma length, pronotum width). Both ergatoid queens and intercastes are novel phenotypes that are assessed for fit to two prominent caste determination models—the standard and hourglass models. Both castes better fit the standard model of caste determination. Lastly, P. eremicus appears to be a narrow endemic that is restricted to a localized area of the Uspallata-Calingasta Valley that lies between the Precordillera and Andean Cordillera of Mendoza Province, Argentina.